Analysis of Forest Types in Relation to Carbon Offset Potential: A Case of Kakamega Rainforest, Kenya - Otuoma, John Millan (JOOUST, 2015)
The emergence of carbon credit markets has stimulated forest restoration efforts as a climate change mitigation strategy. However, a majority of the forest restoration efforts are promoting plantation forest establishment instead of managing forest regrowth. The situation is driven by the assumption that planted trees grow faster than naturally recruited ones and are therefore likely to sequester more carbon than the latter. A number of recent studies have expressed doubts about the perception that faster tree growth leads to a higher rate of carbon sequestration; raising concerns that on-going tree planting efforts may restore forest cover, but fail to achieve the much anticipated carbon offset benefits. This study assessed the tree species diversity, stand structure, aboveground carbon stock and rate of aboveground carbon sequestration among primary, secondary and plantation forest types in Kakamega Rainforest, in regard to their potential to offer carbon offset additionality. The study was carried out in Isecheno, Kibiri and Yala forest blocks, each of which had primary, secondary and plantation forest types. Secondary forest types comprised old-growth, middle-aged and young vegetation stands. Plantation forest types consisted of mixed indigenous, Maesopsis eminii indigenous monoculture and Cupressus lusitanica, Pinus patula and Bischofia javanica exotic monoculture stands. Assessment was carried out using concentric sample plots which were stratified at 30 m, 15 m, 10 m, 5 m and 2 m radius. There were five sample plots per forest type in each forest block giving a total of 135 sample plots. The study employed a nested experimental design. Data were collected on tree species types, tree height and stem diameter at breast height using stratified systematic sampling. Trees were cored at 1.3 m height to obtain wood cores for estimating aboveground carbon. Data were analysed using analysis of variance at 5 % significance level in Genstat statistical software. The results indicated that there was no significant difference in tree species richness among the primary forest, secondary forests and plantation forests. Plantation forests had higher basal area than secondary forests of comparable stand age. Mixed indigenous plantation forests had more aboveground carbon stock than secondary forests. Old-growth secondary forest had more aboveground carbon stock than monoculture plantation forests, but there was no significant difference in carbon stock between middle-aged secondary forest and monoculture plantations. Secondary forests had a higher rate of carbon sequestration than plantations forests in the initial 10 to 30 years of stand growth, but the rate decreased in older stands to an extent that it was not significantly different from that of plantation forests. Findings of the study suggest that plantation forests are undergoing secondary forest succession; faster tree growth in monoculture plantation forests does not lead to a higher rate of carbon sequestration; and mixed indigenous plantations are more likely to achieve carbon offset additionality than monoculture plantations. Thus, forest restoration planting that target carbon offset benefits should employ mixed indigenous tree species, particularly those with high wood density. Where applicable, forest restoration efforts may involve enrichment planting in young secondary forest stands instead of stand-alone plantations. These results are expected to inform investors in carbon offset schemes, forest managers and policy makers on the most appropriate forest restoration approaches with a view to securing carbon offset additionality.